(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article compares gustatory and olfactory lexemes in English and Uzbek within a symmetry-asymmetry framework. The study is based on explanatory dictionaries and contextual material used in the dissertation corpus. Componential, semantic-field, cognitive, contrastive, pragmatic, and statistical methods are applied. In both languages, neutral units such as taste/ta’m and smell/hid or is form the central zones of the corresponding perceptual fields. Symmetry is strongest where the units denote direct sensory recognition or a conventional positive or negative evaluation. Asymmetry increases when taste and smell vocabulary develops figurative meanings connected with aesthetic judgment, personal preference, emotional attitude, social criticism, danger, purity, or moral evaluation. Quantitative analysis identifies 190 English and 107 Uzbek gustatory units, as well as 122 English and 81 Uzbek olfactory units. The results demonstrate a common embodied basis together with differences in lexical density, part-of-speech distribution, evaluative differentiation, and the degree of metaphorical extension.